2009
DOI: 10.1103/physrevb.79.085201
|View full text |Cite
|
Sign up to set email alerts
|

Density functional study of the magnetic coupling inV(TCNE)2

Abstract: A simple model structure of the room-temperature magnetic semiconductor V͑TCNE͒ 2 is proposed on the basis of available experimental data. The structural, electronic, and magnetic properties are investigated using hybrid-exchange density functional theory within periodic boundary conditions. A spin-polarized ferrimagnetic ground state with a total spin of 1 B per formula unit is identified. The analysis of the corresponding electronic band structure and spin distribution reveals strong interactions between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 55 publications
2
46
0
Order By: Relevance
“…The BSs used for this work are all-electron BSs based on pre-existing ones from the literature. The BS for Cu was optimized by Doll and Harrison and used for their study of chlorine adsorption on the Cu(111) surface 25 Electronic exchange and correlation are approximated using the hybrid-exchange B3LYP functional 28,29 , which has previously shown to provide a reliable ground state description of geometric parameters, band structures, and electronic and magnetic properties in a range of strongly correlated (mainly transition metal oxides) materials [30][31][32][33][34][35][36][37] . It has also been reported that the B3LYP functional reproduces the band gap of a wide range of materials including, semiconductors, sulfides and semi-ionic, ionic and transition metal oxides 21,38,39 .…”
Section: Computational Detailsmentioning
confidence: 99%
“…The BSs used for this work are all-electron BSs based on pre-existing ones from the literature. The BS for Cu was optimized by Doll and Harrison and used for their study of chlorine adsorption on the Cu(111) surface 25 Electronic exchange and correlation are approximated using the hybrid-exchange B3LYP functional 28,29 , which has previously shown to provide a reliable ground state description of geometric parameters, band structures, and electronic and magnetic properties in a range of strongly correlated (mainly transition metal oxides) materials [30][31][32][33][34][35][36][37] . It has also been reported that the B3LYP functional reproduces the band gap of a wide range of materials including, semiconductors, sulfides and semi-ionic, ionic and transition metal oxides 21,38,39 .…”
Section: Computational Detailsmentioning
confidence: 99%
“…B3LYP has previously been shown to perform well in the calculations of exchange interactions in inorganic and organic compounds. 17,[24][25][26][27] We adopted the spin Hamiltonian for a one-dimensional…”
Section: à12mentioning
confidence: 99%
“…In order to study the behavior of water on this surface ( 1 ML), we have used hybrid-exchange DFT calculations with the B3LYP functional, which result in an accurate description of the energetics and the electronic structure of periodic systems, [51][52][53][54][55][56][57][58][59][60][61][62][63][64] particularly for transition metal oxides, and, as implemented in the CRYSTAL code, are computationally efficient for large systems. 65 This approach aims to develop a detailed model of interactions for this surface, prior to uncovering the role of defects as well as dependence on surface facet: a thorough investigation of the energetics has been performed, and the method adopted facilitates the analysis of the interactions between adjacent adsorbates.…”
Section: Introductionmentioning
confidence: 99%